CFD/Monte-Carlo neutron transport coupling scheme, application to TRIGA reactor. (December 2017) - Henry, R.; Tiselj, I.; Snoj, L.
Highlights: Water temperature profiles inside the core of TRIGA were measured during operations. Monte Carlo neutron transport code TRIPOLI and fluid dynamics code CFX were coupled. A new computational model of the JSI TRIGA Mark II was built. The coupled model was validated with experimental results. Abstract: A new computational model of the JSI TRIGA Mark II, coupling Monte Carlo neutron transport code TRIPOLI and fluid dynamics code CFX was built and verified with a set of new experimental data. A set of subroutines was developed to allow the communication between the Monte-Carlo transport code and CFD code. First, test of the coupling scheme is presented: for a given thermal power of the reactor, the coupled model numerically reproduced fuel temperature monitored during reactor operation and axial water temperature profile measured in the coolant channels. Then axial temperature profiles in the coolant channels were measured with a newly developed sensor during steady-state operation. Predictions of the coupled model are in expected agreement with experimental data recorded during reactor operations. Influence of the coupling has been investigated.